2018
DOI: 10.21083/partnership.v13i2.4366
|View full text |Cite
|
Sign up to set email alerts
|

Fear at First Sight: Library Anxiety, Race, and Nova Scotia

Abstract: Multidisciplinary research and services have attempted to decrease educational barriersand increase university success for African Canadian students. However, these efforts have put limited focus on the influence of academic libraries on student success. This study examined racial differences in library anxiety and the coping methods undergraduates used in Nova Scotia, Canada. To examine student experiences, this study used a mixed-methods approach with surveys and interviews. In the preliminary phase, survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Students belonging to traditionally marginalized groups may feel isolated, disconnected, and/or like they do not belong to their institution (Mallon, 2019). Fraser (2018) added, "The lack of cultural knowledge among library staff causes additional stress" (p. 7). Book clubs choosing to read diverse material increases their cultural knowledge and signals they value DEI.…”
Section: Access To Materialsmentioning
confidence: 99%
“…Students belonging to traditionally marginalized groups may feel isolated, disconnected, and/or like they do not belong to their institution (Mallon, 2019). Fraser (2018) added, "The lack of cultural knowledge among library staff causes additional stress" (p. 7). Book clubs choosing to read diverse material increases their cultural knowledge and signals they value DEI.…”
Section: Access To Materialsmentioning
confidence: 99%
“…Fraser and Bartlett (2018) conducted a multidisciplinary study on the relationships between library anxiety and the race of the African Canadian students in Nova Scotia, Canada. The data gathered were analysed using thematic analysis for the interview and frequency counts, and percentages as well as inferential statistics for the quantitative data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shelmerdine (2018) explored the work of Carl Rogers on invitational theory as a lens through which to consider library anxiety and concluded that librarianship has close parallels with the helping professions. A study by Fraser and Bartlett (2018) examined racial differences in library anxiety in a Canadian context. Their study found that while Caucasian students entered university with higher levels of library anxiety than African Nova Scotians, library anxiety increased for African Nova Scotians throughout their degree, particularly as they encountered barriers.…”
Section: Building Institutional Literacymentioning
confidence: 99%